REUSABILITY PREDICTION IN AN EDUCATIONAL ENVIRONMENT (International Journal of Food and Nutritional Sciences, 2022)
A great deal of research over the past several years has been devoted to the development of methodologies to create reusable software components but the successfulness of the reuse program is still in its naïve stage. In this paper a novel method for estimating the reusability across an educational domain is presented. The data collected is clustered and the K-means algorithm is applied to the clustered data which is of the matrix form containing the binary data. The relevant data is extracted based on the test data. This method results in identifying the K-mean variants and following the reusability activities for which the reusability factors can be predicted.